Detection of Different Gastrointestinal Parasites in Cows, Sheep, and Goats in Garmian Administration, Kurdistan Region, Iraq - Karim, Mohammed Tharwat; Wahab, Mohammed Abdulkareem; Ameen, Mohmood H. M. (Diyala Journal for Veterinary Sciences, 2023)
Gastrointestinal parasites are parasites with diverse effects on animal health and production. The aims of the study were to isolate, detect, and identify different gastrointestinal parasites in cows, sheep, and goats in Garmian administration area at Sulaimani province, Iraq. The study was conducted on 157 animals (60 Cattle, 43 goats, and 54 sheep). Fresh fecal samples were collected randomly. Out of 157 sampled cows, sheep, and goats, 124 samples were positive for at least one parasite at prevalence 78.980%, in which the rates were cows: 66.666% (40/60) with males 21.666% (13/60) and females 45% (27/60), sheep: 74.074 % ( 44/54) with males 33.333% (18/54) and females 48.148% (26/54), goats: 93.023% (40/43) with males 25.581% (11/43) and females 67.441% (29/43). Different gastrointestinal parasites were identified as Eimeria spp. [sheep (59.259%), cows (35%), and goats (62.790%). Buxtonella spp. in cows was 5%. The types of infection appeared to be highest in a single one (29.299%) than other types. The identified parasites were Eimeria spp. (Oocyct) 50.955%, Trichostrongylus spp. (Egg) 22.292%, Balantidium spp. (Cyst) 14.012%, Ostertagia circumbcinata (Egg) 14.012%, Chabertia ovis (Egg) 10.828%, Monesia spp. (Egg) 9.554%, Marshalgia spp. (Egg) 8.280%, Giardia spp. (Cyst) 6.369%, Skrjabinema spp. (Egg) 3.184%, Toxocara spp. (Egg) 3.184%, Avittelina spp. (Egg) 2.547%, Haemonchus spp. (Egg) 2.547%, Buxtonella spp. (cyst) 1.910%, Dicrocoelum dendriticum (Egg)1.273%, and Bonostomum spp. (Egg), Strongyloid papillosus (Egg), and Trichuris spp. (Egg) were 0.636%. The result of the study showed that different gastrointestinal parasites were presence in cow, sheep, and goats in Garmian Administration, Iraq.